Advances in hepatocellular carcinoma drug resistance models - Xiang, Yien; Wu, Jun; Qin, Hanjiao (Frontiers in Medicine, 2024)
Hepatocellular carcinoma (HCC) is the most common primary liver cancer. Surgery has been the major treatment method for HCC owing to HCC's poor sensitivity to radiotherapy and chemotherapy. However, its effectiveness is limited by postoperative tumour recurrence and metastasis. Systemic therapy is applied to eliminate postoperative residual tumour cells and improve the survival of patients with advanced HCC. Recently, the emergence of various novel targeted and immunotherapeutic drugs has significantly improved the prognosis of advanced HCC. However, targeted and immunological therapies may not always produce complete and long-lasting anti-tumour responses because of tumour heterogeneity and drug resistance. Traditional and patient-derived cell lines or animal models are used to investigate the drug resistance mechanisms of HCC and identify drugs that could reverse the resistance. This study comprehensively reviewed the established methods and applications of in-vivo and in-vitro HCC drug resistance models to further understand the resistance mechanisms in HCC treatment and provide a model basis for possible individualised therapy.